(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2018)
The paper offers a comparison between the most recent case law of the European Court of Human Rights, of the Inter-American Court of Human Rights, of the Court of Justice of the European Union and of the Italian Constitutional Court concerning beginning of life issues with the intent of identifying a shared minimum standard of rights’ protection. Even if this study would methodologically presuppose a “certain” theory of the Constitution, on the merits this comparison highlights a contradictory jurisdictional feeling of attraction-repulsion towards the problem of “embryo’s personalisation”. In the decisions taken into account, it is possible to identify a twofold distinct reductive and expansive trend: this depends on the concept of embryo, that could be intended either as something more than a good (ECtHR and ICtHR) or as something less than a person (Italian Constitutional Court and Court of Justice of the EU).